2019
DOI: 10.1002/cne.24801
|View full text |Cite
|
Sign up to set email alerts
|

PROX1 is a specific and dynamic marker of sacral neural crest cells in the chicken intestine

Abstract: The Enteric Nervous System (ENS) is a complex network constituted of neurons and glial cells that ensures the intrinsic innervation of the gastrointestinal tract. ENS cells originate from vagal and sacral neural crest cells that are initially located at the border of the neural tube. In birds, sacral neural crest cells (sNCCs) first give rise to an extramural ganglionated structure (the so-called Nerve of Remak (NoR)) and to the pelvic plexus. Later, sNCCs enter the colon mesenchyme to colonize and contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Likewise, NOTCH1, a member of NOTCH receptors family, was veri ed expressed in ganglia of the submucosal and myenteric plexus in rat and human ENS [23,24,31]. It was reported that increasing NOTCH signaling in NCCs disabled NCC migrating into the ENS [29]. Equally, oversupply of NOTCH in the enteric mesenchyme led to inadequate neural crest-derived cells migration and colonization [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, NOTCH1, a member of NOTCH receptors family, was veri ed expressed in ganglia of the submucosal and myenteric plexus in rat and human ENS [23,24,31]. It was reported that increasing NOTCH signaling in NCCs disabled NCC migrating into the ENS [29]. Equally, oversupply of NOTCH in the enteric mesenchyme led to inadequate neural crest-derived cells migration and colonization [30].…”
Section: Discussionmentioning
confidence: 99%
“…Prominent among these is still the CNS, where NOTCH1 has been implicated in processes ranging from neuron differentiation, proliferation, maturation and colonization. As for ENS, only a few previous studies demonstrated that PROX1 and NOTCH1 were expressed and played a certain role in enteric neuronal cells in several species [29][30][31]. However, what PROX1/NOTCH1 speci c roles involved in ENS and how the upstream mechanisms regulate are remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To identify genes that define the SMC immaturity, we screened for genes that demonstrated higher level of expression during the process of SMC differentiation using the chick embryo model. We compared profiles of genes expressed in 6-day-old (E6), a stage in which mesenchymal progenitors are not yet differentiated in SMCs (progenitor stage), to those expressed at E9, a stage in which SMCs are differentiated (differentiated stage) [23][24][25]38 and found Platelet-Derived Growth Factor (PDGF) receptor-alpha (PDGFRA) to be highly expressed in the mesenchymal progenitors (Figure 2A). Its profile contrasts to the ones of SOX10 and RET (Enteric Nervous System (ENS) markers), 23,38 KIT and CD44 (Interstitial Cells of Cajal (ICC) markers), 39,40 and CD34 and WNT5A (telocyte markers) 41,42 and differentiated smooth muscle markers (ACTG2, CNN1, FLNA, MYH11 and TAGLN) that harbour highly expression at differentiated stage (Figure 2A).…”
Section: Pdgfra Expression Defines Gastrointestinal Mesenchymal Proge...mentioning
confidence: 99%